Significant advantages for first line treatment with TNF-alpha inhibitors in pediatric patients with inflammatory bowel disease – Data from the multicenter CEDATA-GPGE registry study - Claßen, Merle; de Laffolie, Jan; Claßen, Martin; Schnell, Alexander; Sohrabi, Keywan; Hoerning, André (Frontiers in Pediatrics, 2022)
Background and Aims: In recent years, biological agents, such as anti-TNF- blockers, have been introduced and have shown efficacy in pediatric patients with inflammatory bowel disease (IBD). Here, the prescription mode differentiated into a first/second line application, and efficacy and side effects are evaluated beginning from 2004 until today. Methods: Statistical analyses of the prospective and ongoing CEDATA multicenter registry data from the Society of Pediatric Gastroenterology and Nutrition (GPGE) were performed for patients receiving a biological agent at least once during the period from June 2004 until November 2020 (n = 487). The analyzed parameters were patient demographics, disease extent and behavior, prior or concurrent therapies, duration and outcome of biological therapy, disease-associated complications (e.g., surgery and extraintestinal manifestations), drug-related complications, laboratory parameters (e.g., fecal calprotectin level and ESR) and treatment response as determined by the Physician’s Global Assessment. Results: Crohn’s disease (CD) was present in 71.5% of patients, and 52% were boys. Patients showed high disease activity when receiving a first-line TNF- blocker. After 2016, patients who failed to respond to anti-TNF- induction therapy were treated with off-label biologics (vedolizumab 4.3% and ustekinumab 2.1%). Propensity score matching indicated that patients with CD and higher disease activity benefitted significantly more from early anti-TNF- therapy. This assessment was based on a clinical evaluation and lab parameters related to inflammation compared to delayed second-line treatment. Additionally, first-line treatment resulted in less treatment failure and fewer extraintestinal manifestations during TNF- blockade. Conclusions: First-line treatment with anti-TNF- drugs is effective and safe. An earlier start significantly reduces the risk of treatment failure and is associated with fewer extraintestinal manifestations during longitudinal follow-up.